Novel drill bit with characteristic web shape for high efficiency and accuracy. Issue 1 (2018) - Sugita, Naohiko; Oshima, Masaya; Kimura, Katsuyo; Arai, Giichi; Arai, Koichi
Abstract: This study proposes a novel drill design to reduce the cutting force and improve finished material surfaces. Drilling is a common procedure in manufacturing, and there is an increased demand to shorten the tact time by reducing the cutting force, and by prolonging the tool's life. In this study, a new web shape was proposed based on the proposition to implement an additional cutting edge, complemented by experimental work. The results indicated that the cutting force decreased by more than 20%, and the circularity of the drilled holes was also improved.